2014
DOI: 10.1080/08927014.2014.991319
|View full text |Cite
|
Sign up to set email alerts
|

Red wines and flavonoids diminishStaphylococcus aureusvirulence with anti-biofilm and anti-hemolytic activities

Abstract: The emergence of antibiotic resistant Staphylococcus aureus presents a worldwide problem that requires non-antibiotic strategies. This study investigated the anti-biofilm and anti-hemolytic activities of four red wines and two white wines against three S. aureus strains. All red wines at 0.5-2% significantly inhibited S. aureus biofilm formation and hemolysis by S. aureus, whereas the two white wines had no effect. Furthermore, at these concentrations, red wines did not affect bacterial growth. Analyses of hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 48 publications
6
75
0
2
Order By: Relevance
“…Luteolin, a kind of edible polyphenolic flavonoid, has been proved the antimicrobial effect against MRSA by interfering with QS. [5g,17] It repressed expression of the accessory gene regulator ( agr ) locus, which encode one of S. aureus QS systems . We investigated the transcription of agrA in MRSA by RT‐PCR experiments ( Figure A and Figure S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Luteolin, a kind of edible polyphenolic flavonoid, has been proved the antimicrobial effect against MRSA by interfering with QS. [5g,17] It repressed expression of the accessory gene regulator ( agr ) locus, which encode one of S. aureus QS systems . We investigated the transcription of agrA in MRSA by RT‐PCR experiments ( Figure A and Figure S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…It was also shown that methanol extract from pomegranate, rich in ellagic acid, inhibited the biofilm formation of S. aureus, MRSA, E. coli and C. albicans [124]. Red wines, extensively recognized for their high flavonoid (e.g., quercetin, kaempferol, apigenin, chrysin, fisetin and luteolin) and stilbenoid (e.g., trans-resveratrol) content have proven to be potent inhibitor of S. aureus biofilms [127]. Among the compounds tested, the quercetin exhibited the highest biofilm inhibitory potential.…”
Section: Anti-quorum Sensing and Antibiofilm Effects Of Plant Phenolicsmentioning
confidence: 99%
“…CNMA acts as a quorum sensing inhibitor and probably interferes with the cellular processes of S. aureus, including swarming motility, and might possibly affect the bacterial dissemination in the host. 30,55 Additionally, the prolonged survival rates of the nematodes shown in Figure 5 indicate that CNMA-GNPs have no significant biological toxicity under a long incubation period. The observed no toxicity of CNMA-GNPs prominently suggested that the silica coating does not allow the biological system of the nematode to interact with nanoparticle core directly, thus resulting less toxicity.…”
Section: Survival Of Infected C Elegansmentioning
confidence: 99%
“…30 In addition, biofilm formation by both strains was compared when they were grown in medium alone in 96-well polystyrene plates. Bacteria were stained with carboxyfluorescein diacetate succinimidyl ester (Invitrogen, Molecular probes Inc., Eugene, OR, USA) and visualized at a magnification of 20× using an Ar laser with excitation and emission wavelengths of 488 nm and 500-550 nm, respectively.…”
Section: Evaluation Of Biofilm Growth By Confocal Microscopymentioning
confidence: 99%